2018
DOI: 10.1021/acs.analchem.8b00269
|View full text |Cite
|
Sign up to set email alerts
|

Strand Displacement Probes Combined with Isothermal Nucleic Acid Amplification for Instrument-Free Detection from Complex Samples

Abstract: Sensitive and specific detection of pathogens via nucleic acid amplification is currently constrained to laboratory settings and portable equipment with costly fluorescent detectors. Nucleic acid-detecting lateral flow immunoassay strips (LFIAs) offer a low-cost visual transduction strategy at points of need. Unfortunately, these LFIAs frequently detect amplification byproducts that can yield spurious results which can only be deciphered through statistical analysis. We integrated customizable strand displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 29 publications
0
69
0
Order By: Relevance
“…Rapid molecular biosensing is an emerging application area for synthetic biology, particularly for the on-demand detection of viruses 1-5 microbes 6,7 , metals 8,9 , and pollutants 10,11 in biological or environmental samples. Traditional methods for detecting these analytes of interest require collection of large-volume samples on-site and transportation to centralized laboratories equipped with sophisticated analytical equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid molecular biosensing is an emerging application area for synthetic biology, particularly for the on-demand detection of viruses 1-5 microbes 6,7 , metals 8,9 , and pollutants 10,11 in biological or environmental samples. Traditional methods for detecting these analytes of interest require collection of large-volume samples on-site and transportation to centralized laboratories equipped with sophisticated analytical equipment.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the visible threshold for an untrained user without instruction was quantified at 0.02 grayscale intensity when normalized to the background using a custom MATLAB program. 21,22 Based on this, we used the 0.02 grayscale intensity as the visible threshold for a positive result in our experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Test and control line intensities were analyzed with a custom MATLAB script. 21,22 The visible threshold (the visual cutoff for interpreting a test line as positive) of the background normalized grayscale intensity was set to 0.02 for all signal analyses according to Phillips et al 22 For LOD tests, dilutions of 100 μM probe 3 solution in PBST were used. Tests were run on assembled 2DPNs stored between 1 and 7 days.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such isothermal amplification method, loop-mediated isothermal amplification (LAMP), provides specific and efficient amplification of target nucleic acids by targeting 8 unique sequences (Nagamine et al, 2002). Operable at a single temperature (most efficiently between 65 and 72 °C) (NEB, n.d.; Rolando et al, 2019), LAMP robustly amplifies even in the presence of complex sample matrices, further reducing sample processing and instrumentation requirements (Clayton et al, 2019;Mori and Notomi, 2009;Phillips et al, 2018). To expedite sample preparation steps, such as reverse transcription (RT) of HIV RNA targets, several groups have demonstrated that RT can be performed using the same assay conditions as LAMP (Curtis et al, 2012;Damhorst et al, 2015;Odari et al, 2015;Rudolph et al, 2015).…”
Section: Introductionmentioning
confidence: 99%